2021
DOI: 10.1002/smi.3072
|View full text |Cite
|
Sign up to set email alerts
|

Coping with coronavirus disease 2019: Relationships between coping strategies, benefit finding and well‐being

Abstract: The coronavirus disease 2019 (COVID‐19) pandemic has caused both physical and psychological changes in the general public. The current study aimed to examine the relationship between well‐being and coping strategies in response to the pandemic. Furthermore, we aimed to investigate the mediational role of benefit finding. A total of 521 participants aged 18–65 years were recruited from 29 regions of mainland China. Situation‐specific coping strategies, including support seeking, personal hygiene practice and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…Subjective well-being, including good mental health, also considerably improved in the intervention group as earlier studies suggested [ 35 , 36 ]. Subjective well-being may gradually grow through the experience of benefit finding since benefit finding is closely related to better adaptation and sense making.…”
Section: Discussionsupporting
confidence: 75%
“…Subjective well-being, including good mental health, also considerably improved in the intervention group as earlier studies suggested [ 35 , 36 ]. Subjective well-being may gradually grow through the experience of benefit finding since benefit finding is closely related to better adaptation and sense making.…”
Section: Discussionsupporting
confidence: 75%
“…Religious activities, including praying alone and with others and contacting a pastor or priest, is positively correlated with support and connection, as well as “placing worries in God’s hands”; all of which provide stress relief and additional support among diverse populations including US, European, and East Asian countries [ 6 , 24 , 34 , 37 ] . In addition, approximately 50% of respondents reported contacting a professional health care provider as a coping strategy, which has been shown to be a less common, but still important strategy for maintaining wellbeing during the pandemic [ 19 , 23 , 34 ] . Given our findings and others related to the pandemic reviewed above, remote Alaska residents are commonly engaging in coping strategies associated with greater support, connection, healthy practices, and seeking professional health care support.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the results of the present study confirm and extend previous research, by highlighting the interplay between resilience and adaptive coping strategies, as well as by identifying through participants’ direct narratives the intrapersonal and interpersonal protective factors mitigating the negative psychological consequences of the COVID-19 outbreak [ 58 , 59 , 60 , 61 ]. More specifically, highly resilient students seemed to adopt more adaptive coping strategies, such as identifying positive aspects in a negative condition, a reappraisal strategy defined as benefit finding [ 62 ].…”
Section: Discussionmentioning
confidence: 99%